Physical and Mechanical Properties of Pumice Lightweight Aggregate Concrete - Johari, Mohamad Rifdi; A. Majid, Masni (Recent Trends in Civil Engineering and Built Environment, 2024)
Concrete is now widely used as a construction material all over the world. One of the disadvantages of normal concrete is it has high self-weight which is uneconomical for being a structural material for building. This study was conducted to produce lightweight aggregate concrete (LWAC) by partial replacement of pumice and to investigate the physical and mechanical properties of the concrete by conducting compressing strength, density, workability and water absorption test. There are 4 percentage of pumice concrete block that was tested which are 0%, 10%,20% and 30% with size of 100mm x 100mm x 100mm. For the experiment result, lightweight concrete (LWC) containing pumice has lower strength and workability compare to normal concrete with reduction from 33.5 MPa to 18.8 MPa and from 26 mm to 9 mm respectively. The density also becomes lower where the 30% of pumice replacement that has 1870 kg/m3 can be classified as lightweight concrete. The water absorption of concrete increase as the pumice replacement increases from 3.5 to 10.9%. The LWC containing pumice can be used as structural in low rise material in building.